A Case Report and Review of Postural Orthostatic Tachycardia Syndrome in Pregnancy - Brianna Lide; Sina Haeri (Thieme Medical Publishers, Inc., 2015)
Abstract Purpose Postural orthostatic tachycardia syndrome (POTS) is a form of orthostatic intolerance characterized by an increased heart rate upon transition from supine to standing, and head-up tilt without orthostatic hypotension. Its etiology is multifactorial, and no clear cause has been identified. Common symptoms include light-headedness, blurred vision, weakness, cognitive difficulties, and fatigue and are often accompanied by palpitations, shortness of breath, syncope, or gastrointestinal symptoms. Management includes volume expansion, physical counter maneuvers, and pharmacological agents such as fludrocortisone, midodrine, propranolol, and pyridostigmine. The course of POTS in pregnancy is variable and POTS has not been directly implicated in any adverse outcomes for the mother or fetus. Methods Two cases of POTS in pregnancy are presented, along with a review of the literature for reports of POTS in pregnancy. Results Along with our 2 cases, 10 other case reports were identified and included. Conclusion The course of POTS in pregnancy is variable, and not directly linked to increase perinatal morbidity or mortality. Women can safely undergo regional anesthesia, and vaginal delivery with close monitoring of hemodynamic changes.